The effectiveness of progressive muscle relaxation for air traffic controller in Indonesia - Saleh, Lalu Muhammad; Russeng, Syamsiar S.; Tadjuddin, Istiana; Yanti, Iva Hardi; Syafitri, Nurul Mawaddah; Rahmadani, Yulianah; Yusbud, Mahfuddin (International Journal of Public Health Science (IJPHS), 2025)
Evaluation of progressive muscle relaxation (PMR) intervention testing is deemed necessary for air traffic controllers as their role in controlling aircraft airways requires high focus with stable physical and mental conditions. This study aimed to analyze the effectiveness of progressive muscle relaxation in improving health status, quality of life, and reducing psychological fatigue in air traffic controllers. A quasi-experimental pre-test post-test control group design was employed, involving 184 participants separated into intervention and control groups. The results showed that there was a significant difference in the pulse rate, oxygen level, specific diastolic blood pressure, depression, anxiety, quality of life domains 1 and 2, as well as feelings of fatigue before and after progressive muscle relaxation was implemented with p<0.05 but not in control group at the end of the observation. The Mann-Whitney U-Test results indicated that anxiety and pulse rate are variables reduced significantly in the two groups. It can be concluded that the implementation of PMR is effective to improve the health status, quality of life, and reduce psychological fatigue among controller in Indonesia.